Tubuliferous Thysanoptera in Australia with an enlarged tenth abdominal segment (Phlaeothripidae, Idolothripinae), including six new species - Mound, Laurence A.; Tree, Desley J. (Zootaxa, 2021)
Remarkable structural variation in the tenth abdominal segment of some Phlaeothripidae species is discussed, together with its behavioural significance. Two tropical genera are newly recorded from Australia: in Acallurothrips Bagnall four species are recorded, A. darumbali sp.n., A. erubi sp.n., A. yagara sp.n. and A. nogutii Kurosawa, and in Neosmerinthothrips Schmutz two species are recorded, N. barrowi sp.n. and N. turrbali sp.n. The genus Ozothrips was previously based on five species from New Zealand, but O. meanjini sp.n. is here described from Queensland. Four species of Pygothrips are recorded from Australia, a genus that is widespread in tropical countries.